Metabolic adaptations to morning versus afternoon training: a systematic review and meta-analysis - Galan-Lopez, P.; Casuso, R. A. (Sports Medicine, 2023)
Background: Some physiological responses such as circulating glucose as well as muscle performance show a circadian rhythmicity. In the present study we aimed to quantitatively synthesize the data comparing the metabolic adaptations induced by morning and afternoon training. Methods: PubMed, SCOPUS, and Web of Science databases were systematically searched for studies comparing the metabolic adaptations (> 2 weeks) between morning and afternoon training. A meta-analysis was performed using random-effects models with DerSimonian-Laird methods for fasting blood glucose, hemoglobin A1c (HbAc1), homeostatic model assessment (HOMA), insulin, triglycerides, total cholesterol, low-density lipoprotein (LDL), and high-density lipoprotein (HDL). Results: We identified 9 studies with 11 different populations (n = 450 participants). We found that afternoon exercise was more effective at reducing circulating triglycerides [standardized mean difference (SMD) - 0.32; 95% confidence interval (CI) - 0.616 to - 0.025] than morning training. Moreover, afternoon tended to decrease fasting blood glucose (SMD - 0.24; 95% CI - 0.478 to 0.004) to a greater extent than morning training. Conclusion: Metabolic adaptations to exercise may be dependent on the time of day. Morning training does not show superior effects to afternoon exercise in any of the analyzed outcomes. However, afternoon training is more effective at reducing circulating triglyceride levels and perhaps at reducing fasting blood glucose than morning training.